Studies on Life Fecundity Tables of Tobacco Leaf Eatingcaterpillar, Spodoptera Litura (Fabricius) On Tobacco, Nicotiana Tabacum (Linnaeus) - Patil, R. A; Mehta, D. M; Jat, B. L; Ghetiya, L. V (International Journal of Advances in Life Science and Technology, 2014)
Studies on Life tables of Spodoptera litura, were carried out on bidi tobacco cv ABD-101 under laboratory condition at 26 ± 1 °C temperature at Bidi Tobacco Research Station, Anand Agricultural University, Anand (Gujarat). The results on number of individuals survived during development revealed that there was no mortality during egg stage and the maximum durations of egg, larva and pupa were 4, 22 and 14 days, respectively. The number that survived from 100 eggs to adult emergence was 76. The pre-oviposition period was ranged from 41 to 42 days of pivotal age. Females contributed highest number of progeny (mx = 328.12) in the life cycle on the 45th day of pivotal age. The net reproductive potential (Ro) was 758.93 females with the mean length of generation period (T) of 45.67 days. The innate capacity for increase (rm) and finite rate of increase () were found to be 0.1462 and 1.1574 females/ female/ day, respectively with a weekly multiplication rate (λ)7 of 2.78 times. The hypothetical F2 females were found to be 575974.70. Results on per cent contribution of different growth stages in stable age distribution revealed that the egg stage contributed was maximum (52.64%), while the contribution of larvae, pupae and adults were 45.86, 1.36 and 0.12, respectively at stable age distribution of S. litura on tobacco cv. ABD-101.